The Administrative Authority of Belgian Law in the Europe Modern Political’s Perspective - Albus Samuel Macxel (Jurnal Daulat Hukum, 2023)
This research aims to know that since 1831, the Belgian Constitution allows courts to not apply unlawful administrative acts. This power, established as an obligation by the Supreme Court of Appeal, is called “plea of illegality”, and is guaranteed by Article 159 of the Constitution, which states that “the courts and tribunals shall not apply the provincial and local decrees and general regulations, until they comply with the laws. This research used library/literature research technic. The administrative high court also has the jurisdiction to issue non-binding opinions on the preliminary drafts of regulatory orders of the various federal State governments (federal, regional and community governments). This ex ante review, also carried out with regard to the preliminary drafts of legislative texts, is carried out by the legislative section of the Council of State. In 1991, the Council of State was vested with additional powers as litigants could apply, in summary and interim proceedings, for suspension of the execution of administrative acts, firstly in case of risk of serious irreparable harm, and since 2014, in case of emergency. The result show that last constitutional revision of 2014 tempered the monopoly of the judicial courts in litigation involving civil rights, with the Constitution stipulating that the Council of State has the jurisdiction to rule on the civil effects of its annulment judgments (Const. Art. 144 (2)). It can henceforth award a “restorative allowance” to any litigant who has suffered the effects of the annulled administrative act (consolidated acts on the Council of State, Article 11 bis). It may also indicate the measures to be taken to remedy the illegality sanctioned by its annulment judgments and, if the annulment implies that the authority takes a new decision, it may prescribe a time limit for doing so (consolidated acts, Art 35/1 and 36, 1st).